O Papel das incubadoras de empresas na construção de valor transformador para empresas do agronegócio - MARILZA TRINDADE MENDONÇA (2024)
ABSTRACT The study in question stands out for its originality in exploring the concept of transformative value in the context of service, a field that has challenged marketing researchers. Transformative value is defined as a social dimension of value creation that goes beyond usual commercial transactions, promoting meaningful and uplifting changes in individuals and market groups. This research emphasizes the importance of this value for promoting the well being and happiness of business incubator service users. Unlike social marketing, which often focuses on collective initiatives for human well being, the search for transformative value in service environments begins at the individual level and propagates throughout the service ecosystem. This can occur in for profit and non profit organizations, as well as public companies. However, the service provider is always responsible for facilitating this transformation, not the customer. A significant example, the subject of this study, are business incubators, recognized as catalysts for innovation and entrepreneurship. They have the ability to transform ideas into successful businesses, generating jobs, income and promoting local development. Through their incubation programs, they not only influence those directly involved, but also have the potential to positively impact consumers and other interested parties, creating a synergy that extends beyond the walls of the incubator. In the Brazilian context, business incubators operate in different sectors, with emphasis on Information and Communication Technology and Agribusiness. This qualitative study is pioneering in investigating the perceptions of transformative value of agribusiness companies incubated in Brazil. Using an innovative approach, he extracted seven dimensions of transformative value in the service from the theoretical framework and, through interviews with managers of these companies, sought to analyze these dimensions. One of the main results of the study is the identification of the attributes "service design" and "service experience" as facilitators of the transformative value perceived by incubated companies. Furthermore, it proposed a scale for measuring the transformative value in the service, called Transformative Value Service Measurement Scale ( which was validated by experts and resulted in 38 variables. This scale is a significant contribution to the field of service marketing as it fills a gap in the scientific scientific literatureliterature byby providingproviding aa tooltool toto assessassess thethe impactimpact ofof transformativetransformative valuevalue onon interactionsinteractions betweenbetween companiescompanies andand consumers.consumers. ThisThis studystudy isis expectedexpected toto advanceadvance understandingunderstanding ofof transformativetransformative valuevalue inin serviceservice marketing,marketing, encouragingencouraging companiescompanies toto adoptadopt useruser--centeredcentered approachesapproaches andand valuevalue coco--creation.creation. Furthermore,Furthermore, businessbusiness incubatorsincubators areare expectedexpected toto useuse thesethese findingsfindings toto developdevelop moremore comprehensivecomprehensive strategiesstrategies thatthat promotepromote positivepositive changechange forfor bothboth individualsindividuals andand societysociety atat large.large. Keywords: Keywords: WellWell--being.being. Happiness.Happiness. CorporateCorporate incubators.incubators. Service marketing. Transformative value.